Radio-tomographic images of postmidnight equatorial plasma depletions - Hei, Matthew A. (2014)
For the first time, equatorial plasma depletions (EPDs) have been imaged in the longitude-altitude plane using radiotomography. High-resolution (~10 km) reconstructions of electron density were derived from total electron content (TEC) measurements provided by a receiver array in Peru. TEC data were obtained from VHF/UHF signals transmitted by the C/NOFS CERTO beacon. EPDs generated pre-midnight were observed near dawn. On one night, the bubble densities were highly reduced, 100-1000 km wide, and embedded within a layerlike ionosphere. Three nights later, the EPDs exhibited similar features, but were embedded in a locally uplifted ionosphere. The C/NOFS in-situ instruments detected a dawn depletion where the reconstruction showed lifted EPDs, implying that the postmidnight electric fields raised sections of ionosphere to altitudes where embedded/reactivated fossil-EPDs were detected as dawn depletions. Satellites flying under domelike distortions of the ionosphere may observe these distortions as Broad Plasma Decreases (BPDs).